Diffractive metasurfaces with opposite curvatures of unit cells. (July 2023) - Haldar, Arpita; Joshi, Garima; Vijaya, R.
Abstract: Thin and transparent polymer surfaces, patterned with periodic arrangement of quasi-hemispherical dimples and bulges of equivalent opposite curvatures, are studied for optical diffraction characteristics with visible light. These two-dimensional patterns are replicated from the top surface of colloidal crystals using soft imprint lithography, and possess feature sizes larger than the wavelength and pattern depths/heights significantly lesser than the wavelength. The first-order diffraction pattern, containing bright spots arranged in a hexagonal shape, is analyzed for the diffraction efficiency and angle of diffraction. Concave curvature of the unit cell gives higher diffraction intensity than the convex curvature in the experiment. Analysis with the calculated effective index variation within the thickness of the metasurface supports this observation. Pattern depth/height in the range of 40–100 nm, with an associated effective index variation of 0.09–0.17, is found to be sufficient to observe diffraction from patterned low-index polymeric surfaces in the experiment. Diffraction intensity increases monotonically with pattern depth/height in the low-index substrate. Simulation results are used to extend the studies to higher index substrates, and they possess optimum pattern depth/height that maximizes the diffraction intensity.